Classroom segregation: where do students sit and how is this related to group relations?. (3rd August 2015) - McKeown, Shelley; Stringer, Maurice; Cairns, Ed
Abstract : With increasing ethnic and racial diversity in the classroom, understanding classroom dynamics and the use of space has become increasingly important. In particular, when theoretical perspectives, such as that offered by intergroup contact research, promotes the importance of contact between competing groups to improve relations. Adopting a behavioural approach, the research presented here observed intergroup behaviour between Protestants and Catholics, through seating choice, in three integrated secondary schools in Northern Ireland. In addition, it considered the use of classroom seating plans by teachers. The sample involved students from Year 8 (aged 11–12) and Year 10 (aged 13–14), and their teachers. For observations of seating behaviour, data collection took place at three time points in the school year (September, January and June). Teachers were asked to complete a questionnaire regarding their use of seating plans during the January data collection phase. Seating choice was analysed using a statistical index of segregation. Results found persistent religious segregation over time, despite intergroup contact potential. In addition, the use of teacher enforced seating plans was examined and evaluated, suggesting that they may be restricting natural opportunities for intergroup friendship formation. Findings are discussed in relation to implications for theoretical understandings of contact theory, research methods and policy.